FEATURES OF DEDUSTING BY THE USAGE OF NEEDLE MILLING CUTTER FOR FURNITURE RESTORATION - Dadak, Yuriy; Matsyshyn , Yaroslav; Lyashenyk, Andriy; Dorundyak , Leonid (Forestry, Forest, Paper and Woodworking Industry, 2009)
On to the ground of analysis of wastes descriptions and results of experimental researches of deduster, it is substantiated, in this article, the efficiency of dust collector application with a jalousie disconnector for cleaning of aspirationed air in the process of furniture restoration by needle milling cutter. The needle milling cutter usage for furniture restoration predetermines a specific properties of wastes, which enters in the complement such as wood dust, paint-and-lacquer materials, glues particles, synthetic resins and other components. In connection with diminishing of production volumes and passing to more compact charts of technological processes, lately, the advantage gets to individual movable dust-free-air equipments, which are connected directly to the machine-tool and are computed on its productivity. It is expedient to apply movable dust collector with a jalousie disconnector in which are combined two degrees of cleaning during work process with needle milling cutter. This device owns high efficiency for wood-dust, that it was confirmed by experimental researches with usage of birch wood dust, which has been selected in the cutting process on the circle-saw machine-tool. Results of experimental researches allow us recommend to use the cyclone device with a jalousie disconnector as effective deduster during equipment work on a base of needle milling cutters